COMPARISON OF EASTERN AND WESTERN VARIANTS OF THE KOROGLU EPIC (Scientific journal of the Fergana State University, 2026)
The Koroglu epic is considered one of the most widespread oral narratives among Turkic peoples. Its numerous versions have been recorded across a wide geographic range — from Central Asia and Siberia to Anatolia and the Balkans. These variants are generally classified into two major branches: Eastern and Western. The Eastern variants, predominantly found in Turkestan, typically portray Koroglu (or Goroglu) as a noble-born hero, often born in a symbolic setting such as a tomb — hence the name “son of the grave.” In contrast, Western variants, observed in Azerbaijan, Anatolia, and Bulgaria, depict a hero of humble origins whose father was blinded by enemies — thus earning him the name “Koroglu” (son of the blind). Although the Tobol and Crimean versions are geographically located in the North and East, they share structural and thematic similarities with the Western group. This dichotomy reflects not only regional storytelling traditions but also differing social and ideological values embedded in the epic.